Neurodevelopment at 11 months after starting antiretroviral therapy within 3 weeks of life - Barbara Laughton; Shalena Naidoo; Els F.M.T. Dobbels; Michael J. Boivin; Anita Janse van Rensburg; Richard H. Glashoff; Gert U. van Zyl; Mariana Kruger; Mark F. Cotton (AOSIS, 2019)
Background: Antiretroviral therapy (ART) started between 7 and 12 weeks of age improves neurodevelopmental outcomes in HIV-infected (HIV+) infants, but the impact of even earlier initiation is not yet described. Objective:  We assessed the early neurodevelopment of HIV+ infants who started ART within 21 days of life.  Methods: Participants were enrolled from the public sector birth HIV-diagnosis program. Inclusion criteria included: birth weight 2000g, infant commencing ART 6 weeks and no infant Cytomegalovirus disease. ART included Zidovudine/Lamivudine/Nevirapine for the first 2 weeks, the latter then replaced by Lopinavir/Ritonavir. Once body weight 3kg and gestational age 44 weeks, Abacavir replaced Zidovudine. The Griffiths Mental Development Scales (GMDS) were administered at 10-12 months. Results: Of 29 infants assessed, 23 (79%) were girls. Mean birth weight was 3002 ± 501g. Twenty-four mothers (83%) received ART during pregnancy. Seven (24%) infants were diagnosed HIV+ within 48 hours of birth. Median [IQR] viral load (VL) at diagnosis was 3904 [259;16922] copies/ml, age starting ART was 6.0 [3;10] days and age at VL suppression was 19.1 [15; 36] weeks. At the GMDS assessment nine (31%) participants had detectable VL and 26 (90%) had WHO clinical stage I disease. GMDS was performed at a mean age of 11.5±0.8 months. Mean quotients were within the average range: Global Griffiths score was 103.6±10.9 and mean quotients on the subscales ranged from lowest 95.9±13.4 for Locomotor to highest 112.8±11.3 for Hearing-and-language. Conclusion: Preliminary findings in this small group suggest that early neurodevelopmental scores are within the normal range in infants with perinatal HIV-infection who started ART at a median of 6 days.